Modeling of neutronics and thermal-hydraulic aspects during total instantaneous blockage of central fuel subassembly in a fast reactor. (15th September 2022) - Narendran, Yadu; Natesan, K.; Devan, K.; John Arul, A.; Vikram, G.
Highlights: Development of coupled thermal-hydraulics-neutronics model for the study of total instantaneous blockage (TIB) in sodium-cooled fast reactors. Validation of the models with published results. Calculation of reactivity feedbacks and power changes during the accident. Analysis of TIB with coupled and uncoupled models. Early detection of TIB by core temperature monitoring systems associated with all fuel subassemblies. Abstract: Studies on local flow blockages are of great importance in Sodium cooled Fast Reactors (SFRs). Total instantaneous blockage (TIB) at the inlet of a subassembly (SA) of an SFR is a beyond design basis event that is considered as a theoretical envelope of all small blockages. The extent of core damage propagation is an essential input for the thermal design of the core catcher, which is provided for the collection and cooling of molten core. This study aims to conduct a coupled thermal hydraulics and neutronics analysis of TIB in a medium sized SFR up to the end of fuel melting in the blocked SA. Towards this, a coupled thermal hydraulics and neutronics model is developed by solving heat transfer equations and point kinetics equations numerically. A one-dimensional (1-D) molten clad film motion model is incorporated for simulating the clad relocation dynamics. Using the developed models, a coupled analysis of TIB in a medium sized SFR is carried out. The time of occurrence of key events such as sodium boiling, clad melting, and fuel melting are predicted. The times of detection of the accident by the core temperature monitoring system of neighbouring SA and by the overpower detection signals are also predicted. The time of the TIB detection is earlier than that predicted by a previous study which does not consider reactor power change during the transient. The rise in the sodium outlet temperature beyond the threshold level for the TIB detection is observed for all the fuel SAs before the end of fuel melting in the blocked SA. Thus, assurance towards early detection of TIB by core temperature monitoring system is strengthened.